Programmable 3D optical fields for trapping and nonlinear multiphoton processes - Bautista, Godofredo S. Jr
The advent of ultrafast technology or femtosecond lasers has extended the applications of near-infrared (NIR) lasers from optical manipulation to nonlinear processes particularly in microsurgery and microfabrication. In this dissertation, I propose the use of 3D optical fields that employ programmable optical devices for optical trapping, microsurgery and two-photon photopolymerization.